Theoretical and methodological bases of studying values of youth - Inna Sergeevna Yakunina; Julia Gennadievna Tishchenko; Irina Alexandrovna Tishchenko (Вестник Майкопского государственного технологического университета, 2023)
The values of youth are formed in the conditions of transitivity of modern society, which makes it necessary to pay attention to this problem constantly. The article considers the theoretical and methodological approaches proposed by the classics of Sociology, such as T. Parsons, R. Merton, W. Thomas and F. Znanetsky, E. Durkheim, M. Weber, P. Sorokin, K. Mannheim, R. Inglehart. The concept of “value” is a multidisciplinary one. A sociological approach to this problem involves the study of values and value orientations as components of the social system, which are fundamental elements of culture and act as a mechanism of social regulation. The authors conclude that values are supra-individual, assimilated from the outside, then internalized in the process of socialization and become internal attitudes of a personality. The values acquired in youth hood often remain unchanged throughout life. The ability to exist within the framework of a system of attitudes formed by the society is an important condition for adaptation in it. The relative, concrete historical nature of value orientations, as well as their socio-economic conditionality, are emphasized. The findings are of methodological significance for the analysis of the value world of a younger generation.